The Economic Impact of Artificial Intelligence on Job Creation: Transformative Innovation or Obstacle to Equity? - Arguello Escobar, Sebastian Fernando; Castillo Garzón, Byron Geovanny; Guevara Velastegui, Patricio José; Haro Proaño, Cesar Patricio (Revista Universidad de Guayaquil, 2026)
This research analyzes the impact of artificial intelligence (AI) on employment from a qualitative, interpretive, and hermeneutic-critical perspective. Document analysis is used to explore policies, documentation related to automation, and any other relevant articles on the consequences of automation on the labor market. Critical discourse analysis is used to evaluate sociopolitical and business narratives, their digital transformation, and their respective macro-socioecosystemic impact at the governmental, civil, and private levels. Through thematic coding and comparative analysis, gaps in governance and biases in artificial intelligence management practices are revealed. The results show the existence of contrasting discourses: one focuses on the idea of ​​AI as a driver of technological innovation, while the other warns of its adverse consequences for employment, inequality, and social complexity. The research highlights the importance of AI regulation achieving a balance between technological productivity and social equity. This is key to preventing automation from deepening systemic inequalities in access to employment.